Effect of Couple Therapy Based on the Choice Theory on Social Commitment of Couples - Hossein Abbasi; Seyed Ahmad Ahmadi; Maryam Fatehizadeh; Fatemeh Bahrami (Hamadan University of Medical Sciences, 2017)
Background and Objective: Commitment to spouse, marriage, and family is one of the most important factors ensuring the continuity of marriage and strength of family bonds that has attracted considerable attention in the contemporary family and marriage studies. In this study, we sought to determine the effect of couple therapy based on the choice theory on the social commitment of couples. Materials and Methods: This was a quasi-experimental study with pretest-posttest design and a control group that was performed among volunteer couples visiting Isfahan Counseling and Psychology Centers in Isfahan, Iran, during 2015. The subjects consisted of 32 incompatible couples who were selected through convenience sampling and were randomly assigned into experimental (16 couples) and control (16 couples) groups. Then, the experimental group received nine sessions of group couple therapy during three months on family life skills based on choice theory. It is worth mentioning that the dependent variable was the social commitment of couples evaluated by the dimensions of commitment inventory of Adams and Jones (1997). The collected data were analyzed by multivariate analysis of covariance in SPSS, version 20. Results: At the post-test stage, couple therapy based on choice theory significantly enhanced social commitment in the experimental group compared to the control group (P<0.001). Conclusion: According to the findings of this study, couple therapy based on the choice theory is an effective strategy in promoting commitment and loyalty to spouse, marriage, and family and can decrease and prevent family-related problems and threats such as divorce and marital infidelity.